Fracture Failure Analysis on a Bolt. (November 2020) - Fu, Chunxia; Ren, Facai; Hu, Jiakun
Abstract: A bolt used in the production equipment broke during the use. This paper analyzes the root cause of bolt fracture. Through the analysis on the chemical composition, mechanical properties, microstructure, micro morphology and micro area composition of the broken bolt, it is considered that the physical and chemical properties of the bolt meet the requirements of the standard. Because of the existence of machining cracks, the bolt is affected by the stress in the use process, resulting in fatigue fracture.